Electronic Information Crimes Within the Legal Framework: Tindak Pidana Informasi Elektronik Dalam Kerangka Hukum - Ndururu, Firlius (UPMI Proceeding Series, 2023)
Law Number 11 of 2008 concerning Information and Electronic Transactions (UU ITE) is the first law in the field of information technology and electronic transactions as a much-needed product of legislation and has become the spearhead of laying the foundation for regulations in the field of technology utilization, although now during the implementation of the ITE Law experienced several problems regarding legal certainty regarding criminal provisions after the Constitutional Court decision, protection of personal data and criminal investigations. The method in this study is normative juridical with statutory and conceptual approaches. The government supports the development of IT through the legal and regulatory infrastructure so that the use of IT is carried out safely to prevent its misuse by taking into account the religious and socio-cultural values of the Indonesian people. The side of protection and legal certainty in the use of information technology, media and communication so that it can develop optimally.